Operators Need to Know Basics of Distribution System Water Quality. Issue 4 (4th May 2022) - Adams, Hunter; Ash, Steve; Ikehata, Keisuke; Furatian, Laith; Southard, Mark
Abstract : Understanding how water quality is affected in the distribution system is key to ensuring drinking water quality.